Gas Chromatography-Mass Spectrometry of Volatile Organic Impurities in Whiskey - Nataliya V. Shelekhova; Tamara M. Shelekhova; Liubov I. Skvortsova; Natalya V. Poltavskaya (Техника и технология пищевых производств, 2022)
Alcoholic beverages are complex multicomponent objects. Their quality and safety control is a serious analytical task that requires new, more accurate instrumental methods, e.g., chromatography-mass spectrometry. The research involved domestic and foreign whiskey, other alcoholic beverages, and 40% water-alcohol model solutions. The analytical studies were carried out on a Maestro 7820A gas chromatograph GC with an Agilent Technologies 5975 Series MCD mass selective detector, a G4513A autosampler, and a high polarity FFAP capillary column. The research revealed the optimal parameters of chromatographic separation and mass spectrometric detection. The relative measurement error remained below 25% in the range of 1.0–10 mg/dm3 and 18% in the range of 10–500 mg/dm3. These modes were used to study the composition of the volatile organic impurities. The largest proportion of the total volatile impurities was 34.84–58.08% isoamylol, 17.31–26.76% acetic acid, and 12.50–21.28% isobutanol. Other chemical compounds were not so abundant: 0.34–0.86% isoamyl acetate, 0.13–0.39% 1-butanol, 0.03–0.06% 1-pentanol, 0.40–11.20% ethyl lactate, 0.16–2.74% ethyl caprylate, 1.40–6.44% furfural, 0.18–14.60% ethyl caprate, 0.74–2.97% ethyl laurate, and 1.75–2.39% 2-phenylethanol. The maximal total content of volatile organic impurities was 2040.30 mg/dm3: it was registered in apple samogon. The minimal total content of volatile organic impurities was 392.16 mg/dm3 in the unaged rum distillate sample. The new method proved highly accurate in determining the qualitative and quantitative composition of twelve volatile consumable components in whiskey. The procedure took 17 min; it can be applied to mass concentrations of volatile impurities in such alcoholic beverages as grape-brandy, rum, tequila, brandy, samogon, rum, and various distillates.